Change of dislocations density in single crystals of various types diamonds depending on the growth temperature and rate - Suprun, O.M.; Il'nitskaya, G.D.; Kalenchuk, V.A.; Zanevskii, O.A.; Shevchuk, S.N.; Lysakovskii, V.V. (Functional Materials, 2016)
Single crystals of various types of diamonds have been grown by the melt solution crystallization at high pressures and temperatures. To define the emergences of dislocations onto the {100} and {111} faces, the selective etching of the crystals in KOH and KNO₃ melt has been used. It has been defined that the dislocation density, Nd, in diamond single crystals grown at a low growth rate of 1-2 mg/h at T = 1420-1500°C is 0.8-3·102 cm⁻² and the dislocation densities, Nd, in single crystals grown at temperatures 1280-1450°C and 1280-1350°C at growth rates of 3-5 mg/h and 20-25 mg/h are 1.1-2.2·103 and 1.06-1.35·106 cm⁻², respectively.